2018
DOI: 10.3390/geriatrics3030057
|View full text |Cite
|
Sign up to set email alerts
|

Vet Connect: A Quality Improvement Program to Provide Telehealth Subspecialty Care for Veterans Residing in VA-Contracted Community Nursing Homes

Abstract: Veterans residing in Veterans Health Administration (VA) contracted Community Nursing Homes (CNHs) receive primary care from the CNH they reside in, but often travel to Veterans Affairs Medical Centers (VAMCs) for specialty care services. The Vet Connect project is a quality improvement project aiming to implement video technology to support access to specialty care. Methods: Eight Denver VAMC specialty care providers and three project nurses underwent telehealth training and obtained appropriate equipment. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…The mean age of reported participants was 78.6 years. Three studies were conducted in an exclusive male veterans population [ 14 , 16 , 19 ]. The median study time for the interventions was 12 months (range 5–48 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of reported participants was 78.6 years. Three studies were conducted in an exclusive male veterans population [ 14 , 16 , 19 ]. The median study time for the interventions was 12 months (range 5–48 months.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported on patient or physician satisfaction ( Table 3 ) [ 12 , 13 , 15–17 , 19 , 20 ]. All studies reported that patients were satisfied with the virtual clinic model of care.…”
Section: Resultsmentioning
confidence: 99%
“…VA has also implemented and tested providing telehealth palliative care services. 85,86 Passage of the Veterans E-Health and Telemedicine Support Act of 2017, allowing VA providers to practice telemedicine across state lines, will allow for even further expansion of VA telehealth services for reproductive cancer care. 87 VA recently commissioned and published an evidence map on telehealth services designed for women, with a section dedicated to using telehealth for high-risk breast cancer assessment.…”
Section: Palliative and Supportive Carementioning
confidence: 99%
“…Specialties with evidence demonstrating telehealth effectiveness include oncology, diabetology (including diabetes education services), cardiology, nephrology, psychiatry and addiction services, primary care, geriatrics, and women’s health. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 For instance, DeNicola et al’s systematic review 17 of telehealth interventions in women’s services found improvements in rates of perinatal smoking cessation, breastfeeding and scheduling of office visits, and obstetric outcomes. For the common chronic disease state of obesity, Huang et al’s systematic review 18 found telemedicine visits to be an effective intervention in reducing body weight for patients with or without hypertension and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…For the common chronic disease state of obesity, Huang et al’s systematic review 18 found telemedicine visits to be an effective intervention in reducing body weight for patients with or without hypertension and diabetes. From a combined geriatric and financial perspective, Hale et al 16 demonstrated cost savings by delivering subspecialty care to nursing home residents through telehealth in the Veteran’s Health Administration system.…”
Section: Introductionmentioning
confidence: 99%